Epidemiological trends of pediatric IBD in Italy: A 10-year analysis of the Italian society of pediatric gastroenterology, hepatology and nutrition registry. Issue 4 (April 2022) - Alvisi, Patrizia; Labriola, Flavio; Scarallo, Luca; Gandullia, Paolo; Knafelz, Daniela; Bramuzzo, Matteo; Zuin, Giovanna; Pastore, Maria Rosa; Illiceto, Maria Teresa; Miele, Erasmo; Graziano, Francesco; Romano, Claudio; et al.
Abstract: Introduction: The present study aimed at evaluating Italian epidemiological trends of pediatric inflammatory bowel diseases (IBD) over the period 2009–2018. Materials and methods: Data from 1969 patients enrolled in the Italian Society of Pediatric Gastroenterology, Hepatology and Nutrition Registry, by 49 pediatric IBD centers throughout the country, were analyzed, comparing three different time intervals (2009–2012, 2013–2015, 2016–2018). Results: The number of new IBD diagnoses ranged from 175 to 219 per year, evenly distributed over the examined period of time. From 2009 to 2018, the minimal incidence ranged from 1.59 to 2.04 /10 5 inhabitants aged < 18 years, with an overall slight predominance of ulcerative colitis (UC) over Crohn's disease (CD) (ratio: 1.1). Mean diagnostic delay was 6.8 months for CD and 4.1 months for UC, with a significant reduction for CD when comparing the three-time intervals ( p  =0.008). The most frequent disease locations according to the Paris classification were ileocolonic for CD (41.3%) and pancolitis for UC (54.6%). Conclusions: The minimal incidence rate in Italy seems to have stabilized over the last two decades, even if it has increased when compared to previous reports. UC is still slightly more prevalent than CD in our country. Diagnostic delay significantly decreased for CD, reflecting an improved diagnostic capacity.